2009
DOI: 10.1080/00218460903310070
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Bond Strength of a Highly Cross-Linked Denture Tooth to the Compression-Molded and Injection-Molded Denture Base Polymers

Abstract: This study compared tensile bond strengths between conventional compressionmolded heat (HC)-, auto (AP)-, and microwave-polymerized (MC) poly(methyl methacrylate)-based denture resins and a relatively new injection-molded, microwave-polymerized polyurethane based resin (MI) bonded to a highly cross-linked denture tooth. In the first part of the experiments, denture teeth were used as received. In the second part, they were treated with dichloromethane to see its effect on bonding of conventional denture bases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…The results of the present study revealed that the tooth surface treatment by dichloromethane recorded the highest tensile bond strength values than the other groups (p≤0.05). These results were in agreement with Dogan et al (13) who studied the tensile bond strength of a highly cross-linked denture tooth to the compression-molded and injection-molded denture base polymers and reported that treating tooth surfaces with dichloromethane significantly improved the bond strengths of auto and heat-polymerized resins. These results can be explained by dichloromethane is an organic and non-polymerizable solvent, which swells the surface and permits a diffusion of polymerizable material.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study revealed that the tooth surface treatment by dichloromethane recorded the highest tensile bond strength values than the other groups (p≤0.05). These results were in agreement with Dogan et al (13) who studied the tensile bond strength of a highly cross-linked denture tooth to the compression-molded and injection-molded denture base polymers and reported that treating tooth surfaces with dichloromethane significantly improved the bond strengths of auto and heat-polymerized resins. These results can be explained by dichloromethane is an organic and non-polymerizable solvent, which swells the surface and permits a diffusion of polymerizable material.…”
Section: Discussionsupporting
confidence: 91%
“…There were significant differences in the fracture toughness results between the VP and VF groups (p < 0.001), whereas there was no significant difference between VP and VS groups (p = 0.35), VS and VF groups (p = 0.055), TP and TF groups (p = 0.22). This is similar to the results of previous studies where increased cross-linked PMMA exhibited lower bond strength values [24][25][26]. Although an increase in cross-linking in PMMA increases its mechanical properties, it also increases its resistance to chemical and mechanical abrasion which would decrease the effectiveness of surface treatment methods [27].…”
Section: Discussionsupporting
confidence: 90%